CT

Phân tích các đa thức sau thành nhân tử:

\(e,x^2+y^2-x^2y^2+xy-x-y\)

\(f,x^4+2x^3-4x-4\)

ML
1 tháng 8 2018 lúc 11:52

x2+y2-x2y2+xy-x-y=x2-x2y2+y2-y-x+xy

                            =x(1-y2)+y(y-1)-x(1-y)

                            =x2(y-1)(y+1)+y(y-1)+x(y-1)

                           =-x2(y-1)(y+1)+y(y-1)+x(y-1)

                           =(y-1)(-x2(y+1)+y+x)

Bình luận (0)
ML
1 tháng 8 2018 lúc 12:07

f)    x4+2x2-4x-4=(x3.x+x3.2)-(2x.2+2.2)

                          =x3(x+2)-2(x+2)

                            =(x3-2)(x+2)

Bình luận (0)